Pre- and Post-Liquefaction Behaviors of Manufactured Sand Considering the Particle Shape and Stress History Effects - Zhe Wang; Guanyu Chen; Dazhi Wu; Yao Li; Juntao Hu (Journal of Marine Science and Engineering, 2023)
As the substitution of natural quartz sand (QS), manufactured sand (MS) is highly demanded in the filling and reclamation of foundations in geotechnical engineering, which may be subjected to cyclic shear stresses induced by wave, seismic, and traffic loadings. One of the noticeable distinctions between MS and QS is their particle shape, which has a significant effect on their shear and liquefaction behaviors under the monotonic and cyclic shear stresses, and needs to be further investigated. In this study, the particle shapes of MS and QS were quantitatively characterized by metallurgical microscope tests and digital image processing. Their pre- and post-liquefaction behaviors were evaluated by a series of direct shear tests, cyclic simple shear tests (CSS), and post-liquefaction monotonic shear tests (PMS). The results show that in the CSS test, samples with irregular particles showed stronger liquefaction and shear resistances, indicating that MS was more stable under cyclic shear loadings. In the PMS tests, it was found that the liquefaction and shear resistances of the samples not only increased with the increasing particle irregularity but also with the increasing shear amplitude in the pre-liquefaction stage. Furthermore, quantitative relationships between the particle shape, shear history, and indexes of shear and liquefaction behaviors of the samples were proposed by regression analysis. The research findings could guide the application of MS in offshore and foundation engineering and provide a reference for the selection of MS and its foundation design.